Expression, purification, crystallization and preliminary X-ray diffraction analysis of Arabidopsis thaliana cyclophilin 38 (AtCyp38) - Vasudevan, Dileep (International Union of Crystallography, 2005)
AtCyp38 is one of the highly divergent multidomain cyclophilins from Arabidopsis thaliana. A recombinant form of AtCyp38 (residues 83–437) was expressed in Escherichia coli and purified to homogeneity. The protein was crystallized using the vapour-batch technique with PEG 6000 and t-butanol as precipitants. Crystals of recombinant AtCyp38 diffracted X-rays to better than 2.5 Å resolution at 95 K using a synchrotron-radiation source. The crystal belongs to the C-centred orthorhombic space group C222(1), with unit-cell parameters a = 58.2, b = 95.9, c = 167.5 Å, and contains one molecule in the asymmetric unit. The selenomethionine derivative of the AtCyp38 protein was overexpressed, purified and crystallized in the same space group and data were collected to 3.5 Å at the NSLS synchrotron. The structure is being solved by the MAD method.